The Application of the Theory of Planned Behavior and the Influence of Perceived Organizational Support and Moral Norm on Whistleblowing Intention among Bank B Employees - Dista Hapsa Usari; Fanny Martdianty (Dinasti Publisher, 2025)
Fraud continues to pose a significant challenge worldwide, particularly within both governmental and private-sector institutions. Whistleblowing is widely acknowledged as an effective mechanism for uncovering fraudulent activity; however, many employees refrain from speaking out due to concerns over potential retaliation. This research explores the determinants of whistleblowing intention among employees of Bank B, a state-owned financial institution in Indonesia, by applying the Theory of Planned Behavior which includes components such as attitude, subjective norms, and perceived behavioral control along with additional constructs: Perceived Organizational Support and Moral Norm. A quantitative approach was employed, surveying 244 staff members from the bank’s Head Office and Regional Offices. Data were analyzed using Structural Equation Modeling. The analysis revealed that attitude, perceived behavioral control, organizational support, and moral norms have a significant impact on whistleblowing intention, whereas subjective norms do not. Moreover, whistleblowing intention was found to be a strong predictor of actual whistleblowing behavior. These findings underscore the critical role of cultivating supportive organizational cultures and fostering moral values to promote ethical reporting practices in the banking industry.